NANOMATERIALS BASED ACETYLCHOLINESTERASE BIOSENSORS FOR ORGANOPHOSPHORUS COMPOUNDS DETECTION: REVIEW - Dhull, Vikas; Dilbaghi, Neeraj; Hooda, Vikas (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Due to intense pressure on agriculture for supporting exponentially growing population pesticides are used on an alarming scale. As these pesticides contain Organophosphorus (OP) compounds which are highly toxic and interfere with functioning of enzyme Acetylcholinestrase (AChE) and finally affecting Central Nervous System (CNS). So, there is an urgent need to monitor OP compounds concentration regularly in the marketed food products and even in the environment (water, soil). Here we focus on the different nanomaterials used for the fabrication of the AChE biosensors for detection of OP compounds which is based on inhibition of AChE. The merits and demerits of the different nanomaterials which are being used as supports are also discussed. The mode of detection, detection limit, linearity range, time of incubation, storage stability of the biosensors is also reviewed. Nanomaterial as an important class of supports used for the AChE biosensors due to their valuable properties. Among all the nanomaterials used Gold nanoparticles (AuNPs) have gained an advantage as they are explored with time. Â